Phosphorylation of PLK3 Is Controlled by Protein Phosphatase 6 - Aquino Perez, Cecilia; Palek, Matous; Stolarova, Lenka; von Morgen, Patrick; Macurek, Libor (Cells, 2020)
Polo-like kinases play essential roles in cell cycle control and mitosis. In contrast to other members of this kinase family, PLK3 has been reported to be activated upon cellular stress including DNA damage, hypoxia and osmotic stress. Here we knocked out PLK3 in human non-transformed RPE cells using CRISPR/Cas9-mediated gene editing. Surprisingly, we find that loss of PLK3 does not impair stabilization of HIF1α after hypoxia, phosphorylation of the c-Jun after osmotic stress and dynamics of DNA damage response after exposure to ionizing radiation. Similarly, RNAi-mediated depletion of PLK3 did not impair stress response in human transformed cell lines. Exposure of cells to various forms of stress also did not affect kinase activity of purified EGFP-PLK3. We conclude that PLK3 is largely dispensable for stress response in human cells. Using mass spectrometry, we identify protein phosphatase 6 as a new interacting partner of PLK3. Polo box domain of PLK3 mediates the interaction with the PP6 complex. Finally, we find that PLK3 is phosphorylated at Thr219 in the T-loop and that PP6 constantly dephosphorylates this residue. However, in contrast to PLK1, phosphorylation of Thr219 does not upregulate enzymatic activity of PLK3, suggesting that activation of both kinases is regulated by distinct mechanisms.
Keywords: DNA Damage; proteinfosfatasy; buněčné linie; stress; nádorové supresorové proteiny; protein kinase; lidé; Protein Serine-Threonine Kinases; DNA damage; Cell Line; protein phosphatase; poškození DNA; Tumor Suppressor Proteins; fosforylace; Phosphoprotein Phosphatases; protein-serin-threoninkinasy; Polo-like kinase 3; Phosphorylation; Humans